Dual-functional SERRS and fluorescent aptamer sensor for abscisic acid detection via charged gold nanorods - Zhang, Yanyan; Li, Wei; Zhang, Hao; Wang, Shun; Li, Xiaodong; Zaigham Abbas Naqvi, Syed Muhammad; Hu, Jiandong (Frontiers in Chemistry, 2022)
Abscisic acid (ABA) is a plant hormone, which plays an important role in plant growth, crop cultivation and modern agricultural engineering management. Accordingly, the detection of ABA content combined with new techniques and methods has become a more and more popular problem in the field of agricultural engineering. In this work, a SERS and fluorescence dual-function sensor based on the fluorescence quenching and Raman enhancement properties of gold nanorods (AuNRs) was developed, and applied to the detection of plant hormone ABA. The dual-function reporter molecule Rhodamine isothiocyanate (RBITC) and complementary DNA (cDNA) were modified on AuNRs (AuNRs@RBITC@cDNA) as signal probes and aptamer modified magnetic nanoparticles (Fe3O4MNPs@Apt) as capture probes. Through the specific recognition of ABA aptamer and its complementary chains, an dual-function aptamer sensor based on SERS and fluorescence was constructed. When ABA molecules were present in the detection system, the signal probes were detached from the capture probes due to the preferential binding between aptamer and ABA molecules. SERS signal of the reporter molecules appeared in the supernatant after magnetic separation, and it increased with the increase of ABA concentration. If the etching agent that can etch AuNRs was added to the supernatant, the AuNRs was etching disappeared, then the signal molecules fall off from the AuNRs, and the fluorescence signal intensity would recovered. The intensity of fluorescence signal also increased with the increase of ABA concentration. Thus, the quantitative relationship between ABA concentration and SERS intensity and fluorescence intensity of signal molecules was established. The linear range of SERS detection was 100 fM-0.1 nM，the detection limit was 0.38 fM; The linear range of fluorescence detection was 1 pM-100 nM, the detection limit is 0.33 pM. The constructed dual-effect sensor was used in the recovery laboratory of real ABA samples, the recovery rate was up to 85%-108%.